POD01 Misleading MRI in two recent patients with variant Creutzfeldt–Jakob disease emphasises the importance of tissue diagnosis. Issue 11 (22nd October 2010) - Lukic, A; Wadsworth, J; Brandner, S; Rudge, P; Hyare, H; Collinge, J; Reiniger, L; Mead, S; Gilmore, C; Humberstone, M
Abstract : As the vCJD outbreak evolves we are alert to possible changes in the clinicopathological phenotype, investigations and genetic analysis. MRI typically shows high signal in the pulvinar nucleus on T2W images and has recently been added to the CJD diagnostic criteria. Here we report MRI findings prompting a diagnosis of sporadic CJD by the current WHO criteria in two recent British patients seen by the NHS National Prion Clinic. Quantitative analysis confirmed greater T2W signal hyperintensity in caudate and putamen than the pulvinar. The neuropathological analysis showed characteristic PrP deposition diagnostic of vCJD, in addition to intense and widespread accumulation of abnormally phosphorylated tau protein. PRNP sequencing revealed methionine homozygosity at codon 129 in both patients. Correct diagnosis during life might have been obtained by tonsillar biopsy. Our retrospective blinded review of 60 suspected vCJD patients showed that while MRI had considerable diagnostic value, there were false positive and negative studies, particularly in early vCJD. Tonsillar biopsy had 100% sensitivity and specificity at all disease stages. Biopsy may allow early diagnosis in atypical clinico-pathological phenotypes of vCJD, avoiding unnecessary investigations, and allow rapid inclusion in therapeutic trials. A conclusive diagnosis during life can be of importance to patients and carers.